Sophie's World: A Novel about the History of Philosophy - Gaarder, Jostein (Orion Books Ltd, 1995)
One day Sophie comes home from school to find two questions in her mail: "Who are you?" and "Where does the world come from?" Before she knows it she is enrolled in a correspondence course with a mysterious philosopher. Thus begins Jostein Gaarder's unique novel, which is not only a mystery, but also a complete and entertaining history of philosophy.
Keywords: Juvenile literature-Norway-Philosophy-Fiction